Studies on initial stage of high temperature oxidation of Fe - 9 to 12% Cr alloys in water vapour environment - Kaderi, Akbar; Ani, Mohd Hanafi; Herman, Sukreen Hana; Othman, Raihan (Trans Tech Publications, Switzerland, 2012)
Fe - 9 to 12%Cr alloys are a material for the thick sections boiler components and steam lines of a power plant. The role Fe - 9 to 12%Cr alloys is becoming more prominent in the development of a new generation of Ultra-Supercritical (USC) Power Plant due to the target operating temperature is reaching 620 °C (893 K), in 100% steam condition as well as pressure in excess of 300 bar (30 × 106 Pa). In such condition, the integrity of Fe - 9 to 12%Cr alloys relies on the oxide scale formed during the time of exposure. However due to the high temperature and water vapor condition, it is a well known fact that, the formation of oxide scale is accelerated thus depleting the structural integrity of the Fe - 9 to 12%Cr alloys over the time. Studies show that not only the formation of protective oxide scale was suppressed but the formation of non-protective oxide scale was accelerated instead. Decades of studies done by various groups around the globe has yet to have consensual on the exact mechanism of this phenomenon. Initial stage oxidation of these alloys plays great roles in hope to understand the formation of oxide scale in water vapor condition at high temperature. This paper reviews previous research works to understand the initial stage oxidation of Fe - 9 to 12%Cr alloys at high temperature in water vapor condition.